Effect of Ganoderma lucidum polysaccharides on the growth of Bifidobacterium spp. as assessed using real-time PCR - Shaari, Yamin; Mustafa, Shuhaimi; Ariff, Arbakariya; Abu Bakar, Fatimah; Abdul Khalil, Khalilah; Othaman, Muhammad Anas; Abd Manap, Mohd Yazid (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
The use of component from Ganoderma lucidum as prebiotic source is interesting as the G. lucidum itself was known for more than a decade in the traditional Chinese medicine. In this work, Ganoderma lucidum crude polysaccharides (GLCP) and Polysaccharide-fraction number 2 (PF-2) were used as carbon sources in the fermentation with Bifidobacterium sp. The results showed the potential of prebiotic effect of the G. lucidum extract in batch-culture fermentation based on increment in the growth of bacteria used (0.4-1.5 log10CFU/mL) after 18h fermentation. Fermentation was further done using faecal materials as bacterial inocula and bacterial growth changes were examined using real-time PCR. The results showed the ability of GLCP and PF-2 to support the growth of Bifidobacterium genus with 0.3 and 0.7 log10cells/ml increased, respectively. Interestingly, Lactobacillus which is known as beneficial bacterial genus also showed growth increment with 0.7 and 1 log10cells/ml increased. The competition for carbon sources thus inhibits the growth of potentially harmful genus, Salmonella (0.3 and 0.5 log10cells/ml) in comparison to the control.